The Role of teacher training programs in Developing the Educational Competencies of Mathematics Teachers in Public Schools in Rusaifa Region from their Point of View - Mousa, Suzan Riyad Adli (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the role of teacher training programs in developing the educational competencies of Mathematics teachers in public schools in Rusaifa region from their Point of View, the study used the descriptive analysis approach, questionnaire has been used it consisted from (28) paragraph, the sample of study consisted from (120) female and male teacher. However, the finding of study showed that the role teacher training programs in developing the educational competencies of Mathematics teachers was "High" with average (3.68. out of 5) At the level of the domains, the planning competency domain got an average (3.71) and a high rating, then the evaluation competency domain got an average (3.70), and the implementation competency domain got the last rank with an average (3.62) and an average moderated. The finding also showed there weren’t any significant difference at (α ≤ 0.05) in the degree of role of teacher training programs in developing the educational competencies of Mathematics teachers refers to variable of teacher’s sex. Furthermore, there were significant differences according to principal’s years of experience for less than 10 years.. In light of the results, the researcher recommended the need to continue training and qualifying teachers, and to involve them in the training programs offered by the Ministry of Education.